Techno-economic Analysis of a Wind-Diesel Hybrid Power System in the South Algeria - Allali, Khaireddine; Azzag, El-Bahi; Labar, Hocine (International Journal of Renewable Energy Development, 2015)
The electrical energy is often produced with the help of diesel generators in isolated areas in the Saharan region. While the latter requiring relatively little investment because is generally expensive to exploit due to the transportation to remote areas adds extra cost, significant fuel consumption and relatively high maintenance cost, etc. Moreover, the electricity production by the diesel is ineffective, presents significant environmental risks. But these isolated areas have significant wind energy potential; which is good position for the exploitation of clean and sustainable wind energy. The use of wind-diesel power system is widely recommended especially to reduce fuel consumption and in this way to reduce system operating costs and environmental impact. The subject of this paper is to present the techno-economic analysis of a wind-diesel hybrid power system. In this context, the contribution envisaged with this research is to collaborate on the optimal design of a hybrid power system including a wind turbine generator, a diesel generator and an energy storage system for powering a continuous way an isolated site in the South Algerian installed power of 120 kW.This system has a high control strategy for the management of different power sources (wind, diesel, battery) that depending to weather conditions, especially wind speed values and the power demanded by the consumer load.